The Relationship between Perceived Teachers' Self-disclosure and Out-ofclassroom Communication among Malaysian Undergraduates in a Private Institution of Higher Learning - Aniljeet Singh; Paul Gnanaselvam Pakirnathan; S. Maartandan Suppiah (UiTM Publisher, 2018)
This quantitative study was conducted to determine whether a significant relationship exists between perceived teachers' self-disclosure and students' out of classroom communication with teachers in a Malaysian private institution of higher learning. A survey consisting of two questionnaires, namely the Perceived Teacher's Self-Disclosure scale designed by Cayanus and Martin (2008) as well as Knapp and Martin's (2002) Out-of-Classroom Communication Scale were collected from 144 final year undergraduates from a Malaysian private institution of higher learning. Using the SPSS, the Pearson product-moment correlation coefficient, independent-samples t-test and one-way between-groups ANOVA with post-hoc tests were used to analyze the data. The findings indicated a positive relationship between the dimensions of amount and relevance in perceived teachers' self-disclosure and students' out of classroom communication. There was no significant difference recorded between gender, with perceived teachers' self-disclosure and students' out of classroom communication. Besides, there was also no significant difference recorded between age, with perceived teachers' self-disclosure and students' out of classroom communication. The study concludes that Malaysian undergraduates' perceptions towards teachers' self-disclosure influences the out of classroom communication with teachers.